ANALISIS TINGKAT BAHAYA, KERENTANAN DAN RISIKO PERUBAHAN IKLIM: STUDI KOMPARATIF PETANI PADI JAWA BARAT DAN JAWA TIMUR - Bobby Rachmat Saefudin; Tuhpawana Priatna Sendjaja; Dini Rochdiani; Ronnie Susman Natawidjaja; Elly Rasmikayati (Universitas Galuh Ciamis, 2021)
The impact of climate change on the agricultural sector, especially rice, has been very pronounced. Rice farmers in Indonesia who are mostly small farmers, are certainly the first to be affected by the risks of climate change. The study aims to analyze and compare the level of climate change hazard, vulnerability and risk to rice farmers in West Java and East Java. This study used a total of 600 farmers from West Java and East Java who were determined using a multistage stratified random sampling technique. The data analysis technique used was the analysis model for the climate change hazard, vulnerabilityy and risk level and the Mann-Whitney U test. The results showed that rice farmers in West Java had a significantly greater level of climate change hazards than rice farmers in East Java, but the level of climate change vulnerability for rice farmers in West Java is significantly lower than that of rice farmers in East Java. The results of climate change risk level analysis show that there is no significant difference between West Java and East Java farmers in terms of the level of climate change risk. Both have low to moderate levels of climate change risk.